An application of fuzzy AHP for ranking human resources development indices - Mehdi Paktinat; Abolfazl Danaei (Management Science Letters)
The Human Development Index (HDI) is a composite statistic of life expectancy, education, and income indices, which is implemented to rank countries into different items of human development including life expectancy, education, living standards. This paper uses fuzzy analytical hierarchy process (AHP) to rank five influencing factors including income, culture, healthcare, knowledge and civil rights in Iran. Using a questionnaire in linguistic form, the study asks some experts to make judgment about the relative importance of each pair of five items and it ranks them based on fuzzy AHP technique. The results indicate that income is number priority followed by knowledge, culture, civil rights and healthcare affairs.